2018
DOI: 10.1038/s41467-018-04313-6
|View full text |Cite
|
Sign up to set email alerts
|

STT3-dependent PD-L1 accumulation on cancer stem cells promotes immune evasion

Abstract: Enriched PD-L1 expression in cancer stem-like cells (CSCs) contributes to CSC immune evasion. However, the mechanisms underlying PD-L1 enrichment in CSCs remain unclear. Here, we demonstrate that epithelial–mesenchymal transition (EMT) enriches PD-L1 in CSCs by the EMT/β-catenin/STT3/PD-L1 signaling axis, in which EMT transcriptionally induces N-glycosyltransferase STT3 through β-catenin, and subsequent STT3-dependent PD-L1 N-glycosylation stabilizes and upregulates PD-L1. The axis is also utilized by the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
283
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(289 citation statements)
references
References 62 publications
5
283
1
Order By: Relevance
“…BCSCs are resistant to chemotherapy and radiation [2,6,41,43] and recent studies demonstrated that BCSCs escape from innate and adaptive immune responses, which suggests that BCSCs are resistant to immunotherapy as well [44][45][46][47][48]. These findings underscore the importance of developing novel approaches that make BCSCs as sensitive as non-BCSCs to conventional therapies and immunotherapy in order to develop successful and curative treatments for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…BCSCs are resistant to chemotherapy and radiation [2,6,41,43] and recent studies demonstrated that BCSCs escape from innate and adaptive immune responses, which suggests that BCSCs are resistant to immunotherapy as well [44][45][46][47][48]. These findings underscore the importance of developing novel approaches that make BCSCs as sensitive as non-BCSCs to conventional therapies and immunotherapy in order to develop successful and curative treatments for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding regsrding CSC maintenance is that programmed death ligand 1 (PD-L1, also known as CD274) could stimulate CSC expansion via the high mobility group A (HMGA)-dependent Akt and ERK pathways [140]. PD-L1 in CSCs also confers immune evasion, thereby sustaining the tumorigenesis of CSCs [141]. Recently, miR-873-5p was shown to target PD-L1, thus attenuating breast cancer stemness [142] (Table 4).…”
Section: Mirnas Regulating Nf-κb Signaling and Pd-l1mentioning
confidence: 99%
“…Over the last two decades, human tumor cells with stem cell properties (stemness) have been identified and demonstrated to initiate tumorigenesis and accelerate progression, coupled with therapy resistance, immune evasion and distant metastases [5][6][7][8][9][10][11][12] . However, targeting cancer stemness has yet to be widely achieved in the cancer clinic and therefore demands a better understanding and identification of targetable stemness regulators.…”
Section: Introductionmentioning
confidence: 99%